Exam Survival Guide: Physical Chemistry - Vogt, Jochen (Springer International Publishing : Imprint: Springer, 2017)
A text- and exercise book for physical chemistry students! This book deals with the fundamental aspects of physical chemistry taught at the undergraduate level in chemistry and the engineering sciences in a compact and practice-oriented form. Numerous problems and detailed solutions offer the possibility of an in-depth reflection of topics like chemical thermodynamics and kinetics, atomic structure and spectroscopy. Every chapter starts with a recapitulation of important background information, before leading over to representative exercises and problems. Detailed descriptions systematically present and explain the solutions to the problems, so that readers can carefully check their own solutions and get clear-cut introductions on how to approach similar problems systematically. The book addresses students at the (upper) undergraduate level, as well as tutors and teachers. It is a rich source of exercises for exam preparation and can be used alongside classical textbooks. Furthermore it can serve teachers and tutors for the conception of their lessons. Its well-thought-through presentation, structure and design make the book appeal to everybody who wants to succeed with the physical chemistry lessons and exercises.
Keywords: Chemistry.; Spectroscopy.; Physical chemistry.; Electrochemistry.; Thermodynamics.; elektronické knihy; electronic books